2021
DOI: 10.1080/21655979.2021.1989261
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanisms of signal pathway activating effect of E2F-1/NF-κB/GSK-3β on cognitive dysfunction of Alzheimer rats

Abstract: Alzheimer disease (AD) seriously harms human health and its onset is insidious. Therefore, it is of great significance to find out the pathogenesis of AD disease for improving the prevention and treatment effect of the disease. The study drew attention to the influence of E2F-1/NF-κB/GSK-3β signaling pathway on cognitive dysfunction of Alzheimer rats. 60 specific pathogen-free (SPF) SD rats were selected as research subjects. The, the AD model was created by injecting Aβ1-42 into hippocampus CA1 region of AD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In recent years, the production of grouper culture has been rising, and the scale of culture has been expanding. However, the rapid development of the intensive culture of grouper may induce oxidative stress in fish, caused by aquatic animals, and affect the antioxidant protection capacity of aquatic animals [1].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the production of grouper culture has been rising, and the scale of culture has been expanding. However, the rapid development of the intensive culture of grouper may induce oxidative stress in fish, caused by aquatic animals, and affect the antioxidant protection capacity of aquatic animals [1].…”
Section: Introductionmentioning
confidence: 99%
“…Rs10206871, mapped to the enhancer of SERTAD2, was found to have shared genetic effects on both EGF and inferior lateral ventricles. SERTAD2 could enhance E2F transcription factor activity to control both in ammatory and neuronal cell cycling pathways [37]. We also identi ed SNPs that in uence WMH changes over the 12-month follow-up period, as well as CD40L and EGF.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of Aβ in primary cortical neurons leads to a 54% drop in PRMT5 expression and a 70% increase in E2F-1 expression. Studies have revealed that the protein Tau in the brain tissues of AD patients has detectable phosphorylation changes at Thr231, Ser235, Ser396, Tyr394, Ser404, and Thr181 [ 53 ], suggesting that the protein is intimately linked to neurodegeneration. Further, activation of GSK-3β results in the phosphorylation of Tau at the Ser404 location and leads to the development of AD [ 54 ].…”
Section: Role Of Prmts In Alzheimer’s Diseasementioning
confidence: 99%